Synthesis, characterization and fabrication of porous carboxymethyl cellulosestarch based bio-composite materials - Nur Nadia, Mohd Nasir (2017)
Bio-composite polymer have an important role in many applications. Bio-composite consists of the perfect combination of natural polymers that are biodegradability, least expensive cost and non-toxicity material. The natural polymer combination that have been used in this research are modified cellulose, which is carboxymethyl cellulose (CMC), and starch. In this study, CMC and corn starch will be blend at different weight ratios (100:0, 50:50, 60:40, 30:70, 0:100) by using water as the only solvent. The CMC, corn starch and mixture of CMC/corn starch will be undergo freeze-drying process to produce highly porous biopolymers substrates. Freeze-drying is an easy and convenient technique to produce highly interconnected pores, favourable in tissue engineering. This methods involves the removal of water or any other solvent without damaging of a frozen product by a process called sublimation. All the samples will be physically and thermally characterized by using Rheometer, SEM, ATR-FTIR and TGA. ATR-FTR spectroscopy, has been used to study the functional group of CMC/starch blend polymer solution. In ATR-FTIR study, the changes to the infrared bands, associated with the C-O stretch coupled to the C-C stretch and O-H deformation, were significant and this further supports the strong hydrogen bonding of CMC to the solid surface. SEM have been used to investigate the functional group and porous structure characteristics of the prepared sample. Under SEM testing, the images of each sample shows the different porous structure were obtained by varying the different content of CMC/starch. The measurement of porous scaffolds were assessed with ImageJ, the results showed the increasing of pore size with the addition of CMC content while the granular morphology were showed that the distribution is increased with the amount of corn starch. . Next, TGA and derivatives thermogravimetry (DTG) were carried out for studying the thermal properties of CMC/starch freeze-dried scaffolds. TGA/DTG curve shows that the weight loss of the sample decreased due to the increasing of the temperature of heating. The viscosity of CMC/starch blends polymer solution has been testing by using a rheometer. The sample solution with higher content of CMC showed that the viscosity decrease due to the increasing of shear rate.